Sir Peter Pett, Sceptical Toryism and the Science of Toleration in the 1680s - Goldie, Mark (Studies in church history, 1984)
In the charged atmosphere of religious xenophobia in England in the 1680s it was an unusual person who could survey the state of Christendom and the zealotry of his fellow countrymen with a detached eye. Such a one was Sir Peter Pett, ‘a virtuoso, and a great scholar, and Fellow of the Royal Society’. His vast and inchoate book, The Happy Future State of England, is eirenic, Erastian and Hobbesian in outlook. It is also an exercise in the fledgling science of ‘political arithmetic’. With the panoply of scientific reasoning it predicted the imminence of a secular age in which the knot of politics and religion would be untied. This paper will first sketch the background to this book, then examine its account of the state of Catholicism and dissent, and lastly appraise its claim that ‘a science of politics’ could provide a solvent of religious persecution.